Muballigh Online Reception of Hadith Tasyabbuh and Intention (Controversion of Wishing Merry Christmas): Penerimaan Mubaligh Online atas Hadis Tasyabbuh dan Niat (Kontroversi Mengucapkan Selamat Natal) - Nur Jannah, Safri; Moh. Isbat Alfan Ghoffari (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The law of wishing Merry Christmas by Muslims is always debated and can be an indicator to determine the level of religious moderation. There are at least three groups in the legal debate wishing Merry Christmas, namely groups that allow, prohibit, and situational. One of the figures that has attracted public attention regarding the law of wishing Merry Christmas is Dr. Buya Ar Razzy through Deddy Corbuzier’s YouTube podcast. By applying Stuart Hall’s reception theory, this study found that the reception of hadith tasyabbuh and intentions in the podcast are included in the negotiation category. This welcoming pattern is proof that ar Razzy is trying to spread a moderate mindset. This moderation has implications for the creation of cyber Muslims who are wiser in responding to differences. This is reflected in the digital response in the podcast comments. In addition, the emergence of many video clips on YouTube Shorts with positive narratives is another proof that more and more parties agree with the moderate opinion and mission presented by ar Razzy.